PENGARUH BETA, DEBT TO EQUITY RATIO, EARNING PER SHARE, UKURAN PERUSAHAAN TERHADAP RETURN SAHAM (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2012) (Students' Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of beta (systematic risk), Debt to Equity Ratio,Earning Per Share and firm size on stock returns. This study uses secondary data obtained from the annual report. Samples were selected using purposive sampling technique to the study period 2010-2012. Data were analyzed using multiple linear regression analysis. Results of hypothesis testing showed that beta (systematic risk) and a significant negatif effect on stock returns. Debt to Equity Ratio and no significant positif effect on stock returns. Earning Per Share positive and significant effect on stock returns. The size of the company negative and no significant effect on stock returns.Keywords: beta (systematic risk), Debt to Equity Ratio, Earning Per Share, firm size and stock returns